2004
DOI: 10.1021/cm034990+
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Hydrogen Sulfide−Germanium Sulfide System

Abstract: In the present work, the (x)H2S + (1−x)GeS2 system has been systematically investigated to determine the incorporation of hydrogen into the tetrahedral germanium sulfide network. Reactions between gaseous H2S and glassy-GeS2 have been explored over a range of temperatures and pressures. Reactions for shorter times and lower temperatures (ambient through 250 °C) produced the protonated thiogermanic acid H4Ge4S10 with an adamantane-like microstructure. In contrast, longer reaction times produced the unprotonated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The peaks at 346 and 348 cm À1 are assigned to the Ge-S-Ge A 1 symmetric stretch mode, while that at 374 cm À1 is assigned to the so-called A c 1 companion stretch mode [31][32][33][34]. The band at 415 cm À1 is attributed to GeS À , arising from a possible cleavage of Ge-S-Ge bridges [35,36], while those at 437-440 cm À1 are assigned to the stretching mode of S-S dimers at the surface [32,34]. For the crystalline aerogels, all of these bands are also seen, but there are additional bands at 520, 774 and 881 cm À1 (Fig.…”
Section: Speciation In Amorphous and Crystalline Ges X Aerogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peaks at 346 and 348 cm À1 are assigned to the Ge-S-Ge A 1 symmetric stretch mode, while that at 374 cm À1 is assigned to the so-called A c 1 companion stretch mode [31][32][33][34]. The band at 415 cm À1 is attributed to GeS À , arising from a possible cleavage of Ge-S-Ge bridges [35,36], while those at 437-440 cm À1 are assigned to the stretching mode of S-S dimers at the surface [32,34]. For the crystalline aerogels, all of these bands are also seen, but there are additional bands at 520, 774 and 881 cm À1 (Fig.…”
Section: Speciation In Amorphous and Crystalline Ges X Aerogelsmentioning
confidence: 99%
“…Stanić et al have also reported a range of stoichiometries for the Ge:S xerogels that vary from 1:1.2 to 1:2.6 for R = 1.32 and 10, respectively [25]. Additionally, non-stoichiometric GeS x glasses are routinely prepared by melting elemental Ge and S in varying ratios [34,35]. Unlike SiO 2 -gels and aerogels, the GeS x materials produced here could not be prepared as monoliths (even at higher concentration of H 2 S, R = 3.6), but instead formed as a fluffy white powder.…”
Section: Amorphous Samples: Aerogel Vs Xerogelmentioning
confidence: 99%
“…Decomposition of the inorganic part is highly improbable. As a matter of fact, TG analysis of amorphous GeS 2 reported by Sutherland et al18 shows that the compound is stable at least up to 500 °C. The weight loss is therefore attributed to the particle decomposition and loss of its organic moiety.…”
Section: Resultsmentioning
confidence: 95%
“…The relatively low value of Poisson’s ratio (υ = 0.28) for GeS 2 glass indicates an intermediate between the highly cross-linked 3D network and the weakly correlated 2D network. , This is likely also the reason why it is so difficult to prepare pure crystalline β-GeS 2 by crystallization of a glass precursor by a thermal treatment. It seems that the final product is always contaminated by the α-GeS 2 phase, even when the treatment takes place well below the β → α transition range, except the glassy precursor, which has been carefully purified by distillation. , Therefore, for synthesis of high purity β-GeS 2 , the high-pressure hydrothermal synthesis described by Wang and Horn or the hydrogen sulfide synthesis described by Sutherland et al , should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the final product is always contaminated by the α-GeS 2 phase, even when the treatment takes place well below the β → α transition range, except the glassy precursor, which has been carefully purified by distillation. 21,37 Therefore, for synthesis of high purity β-GeS 2 , the high-pressure hydrothermal synthesis described by Wang and Horn 5 or the hydrogen sulfide synthesis described by Sutherland et al 43,44 should be considered. Significantly higher crystal growth velocity of β-GeS 2 in the amorphous thin film vs bulk surface connected with weaker viscous flow dependence clearly indicates that the molecular crystal growth rate and viscosity are probably decoupled; this is discussed further, below.…”
Section: The Journal Of Physical Chemistrymentioning
confidence: 99%